Upland rice potential in Senegal - Rebolledo, Camila; Adam, M.; Audebert, A.; Daff, A.; Balde, A. (International Center for Agricultural Research in the Dry Areas, 2024)
Rice production is a priority for Senegalese food sovereignty, and the country has invested heavily for the last three decades in irrigated rice culture, with new large irrigation perimeters in the Senegal valley and Anambe basin, and efforts to increase rice productivity, including diverse subsidy, research and extension support. In the south of Senegal, it is estimated that 350 000 ha could be cropped with rice, 80% of this area is in the Casamance and Senegal Eastern region. Climate change and rising costs of maintenance of irrigation systems are nudging Senegal to rethink their rice production systems, with possibly a greater importance to more water-efficient and climate smart rice production, including upland rice. This ClimBeR report, under the crop diversification policy pathway (work package 3 / Senegal), provides evidence and methodology for better decisions on mapping where upland rice systems could be scaled in Casamance, as a climate smart and water efficient solution for local rice farmers.